Keeping social distance in a classroom while interacting via a telepresence robot: a pilot study - Marmor, Kristel; Leoste, Janika; Heidmets, Mati; Kangur, Katrin; Rebane, Martin; Pöial, Jaanus; Kasuk, Tiina (Frontiers in Neurorobotics, 2024)
The use of various telecommunication tools has grown significantly. However, many of these tools (e.g., computer-based teleconferencing) are problematic in relaying non-verbal human communication. Telepresence robots (TPRs) are seen as telecommunication tools that can support non-verbal communication. In this paper, we examine the usability of TPRs, and communication distance related behavioral realism in communication situations between physically present persons and a TPR-mediated person. 24 participants, who played out 36 communication situations with TPRs, were observed and interviewed. The results indicate that TPR-mediated people, especially women, choose shorter than normal communication distances. The type of the robot did not influence the choice of communication distance. The participants perceived the use of TPRs positively as a feasible telecommunication method.